(untitled) (Boston, 1997)
Reviews the relatively new practice of anesthesia administration outside the traditional operating room suite. Examines developments in telemedicine, telesurgery, and teleanesthesia.
Keywords: Anesthesia,Hospitals,Anesthesiology,Gây mê,Bệnh viện,Gây mê học; Anesthesia services,Practise,Dịch vụ gây mê,Thực hành